Extended Spectrum Beta-Lactamase Production By Acinetobacter baumannii Isolated From Hospital Environment - Maysa S. ALshukri; Aalaa F. Abass; Haneen M.Al-Rubaie (International Journal of Antibiotics, 2024)
Extended spectrum β-lactamases production was determined by Double Disc synergy test for twenty one bacterial isolates of Acinetobacter bumannii isolated from the hospital environment. This study investigates the prevalence, genetic mechanisms, and clinical implications of ESBL production by A. baumannii. We employed molecular techniques to identify and characterize ESBL genes in clinical isolates, alongside evaluating their susceptibility profiles against a range of antibiotics. These resistant strains were notably associated with severe infections and poor clinical outcomes. The results underscore the urgent need for robust surveillance and novel therapeutic strategies to address the growing threat of ESBL-producing A. baumannii. The results showed 38.09% (8/21) of isolates were ESBL-positive, distributed between 33.33% (4/12) ESBL-positive environmental A. baumannii isolates and 44.44% (4/9) ESBL-positive clinical A. baumannii isolates. Based on statistical analysis, there was no significant correlation found between the isolates source and the production of ESBL (P>0.05). Detection of gene encoding a class A extended spectrum β-lactamase blaPER-1, Integron genes (int1, and int2 genes) in 19 different environmental and clinical A. baumannii isolates by Polymerase chain reaction technique revealed genes frequencies were 42.1% (8/19), 100% (19/19), and 57.89% (11/19) respectively. The results analysis exhibited that the frequency of genes had no significant differences (P>0.05) between environmental and clinical isolates of A. baumannii.
Keywords: Acinetobacter baumannii; Antibiotic Susceptibility; Genetic Mechanisms; blaPER-1 gene; extended spectrum beta-lactamase